PENGARUH SARANA PRASARANA DAN PROFESIONALISME DOSEN TERHADAP PRESTASI BELAJAR MAHASISWA - Abdul Kadir (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
This research is quantitative positivistic, aims to describe 1) lecturer professionalism, 2) facilities and infrastructure, 3) academic atmosphere, and student learning achievement of the State Islamic Institute of Palopo, and to test the correlation between 5) lecturer professionalism and student learning achievement of the State Islamic Institute of Palopo, 6) facilities and infrastructure and student learning achievement of the State Islamic Institute of Palopo, 7) academic atmosphere and student learning achievement of the State Islamic Institute of Palopo, finally testing the multi-correlation between 8) lecturer professionalism, facilities and infrastructure, academic atmosphere on student learning achievement of the State Islamic Institute of Palopo. This study uses questionnaires, observation guidelines, and lists and tables as measuring tools, with a population consisting of 12,000 students. The sample was determined using the Slovin formula, resulting in a total of 389 respondents. The descriptive hypothesis test produced the following conclusions: 1) The average score of lecturer professionalism is 79.90%, which is included in the high category. This shows that lecturers at the State Islamic Institute of Palopo apply good professionalism indicators. 2) The average score of facilities and infrastructure reached 72.70%, also in the high category, which shows that students at the State Islamic Institute of Palopo utilise facilities and infrastructure optimally during the lecture process. 3) The average score of the academic atmosphere was 78%, which is considered high, proving that the campus atmosphere at the State Islamic Institute of Palopo supports a conducive environment. 4) The average score of learning achievement was 79%, included in the high category, which shows that student achievement at the State Islamic Institute of Palopo is very satisfying.